Anchoring of black phosphorus quantum dots onto WO3 nanowires to boost photocatalytic CO2 conversion into solar fuels. Issue 56 (10th June 2020) - Gao, Wa; Bai, Xiaowan; Gao, Yuying; Liu, Jinqiu; He, Huichao; Yang, Yong; Han, Qiutong; Wang, Xiaoyong; Wu, Xinglong; Wang, Jinlan; Fan, Fengtao; Zhou, Yong; et al.
Abstract : A 0D–1D direct Z-scheme heterojunction consisting of black phosphorus quantum dots (BPQDs) anchored onto WO3 nanowires was well designed. Abstract : A 0D–1D direct Z-scheme heterojunction consisting of black phosphorus quantum dots (BPQDs) anchored onto WO3 nanowires was well designed. Kelvin probe force microscopy studies provide direct evidence for charge transfer and separation between BPQDs and WO3 in a single nanowire, confirming the Z-scheme model. The BPQD–WO3 heterojunction displays excellent performance of photocatalytic reduction of CO2, exhibiting not only highly efficient carbon monoxide solar fuel conversion, but also a significant amount of ethylene (C2 H4 ), a highly value-added hydrocarbon species, rarely reported in previous photocatalysis processes. Both experimental and theoretical calculations demonstrate that BPQD plays a critical role in photocatalytic formation of C2 H4 from CO2 .